PCI DSS: A Critical Analysis of Implementation, Effectiveness, and Legislative Impact in Payment Card Security - Srinivas Chippagiri,; Apoorva Ramesh, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The Payment Card Industry Data Security Standard (PCI DSS) has emerged as a pivotal framework in securing payment card transactions across global financial systems. This article presents a comprehensive analysis of PCI DSS, examining its evolution from disparate security programs to a unified standard, technical framework, and implementation challenges across different merchant levels. The article evaluates the effectiveness of the compliance validation mechanisms, including self-assessment questionnaires and third-party assessments, while analyzing the standard's incorporation into state legislation and its legal implications. This article reveals a complex relationship between compliance validation and actual security effectiveness by examining documented security breaches and industry responses. The findings indicate significant gaps between formal compliance and real-world security outcomes, highlighting the need for a more dynamic approach to payment card security. This article contributes to the ongoing discourse on payment security standards by identifying key challenges in implementation and suggesting potential areas for improvement in future iterations of the standard.
Keywords: Payment Card Security; PCI DSS Compliance; Information Security Standards; Data Protection Regulations; Security Assessment Frameworks